1997
DOI: 10.1177/039139889702000508
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Blood flow Behaviour in the Valved Catheter of the PUCA-Pump, a LVAD

Abstract: Mechanical heart assistance, performed by the PUlsatile CAtheter (PUCA) pump, chronologically takes place by sucking blood from the left ventricle and ejecting it into the ascending aorta. Within the pump activity the problem of hemolysis and clotting is encountered. In this study the influence of valve geometry on blood cell damage and stagnant zones has been investigated. A variable valve length coupled to a catheter ejection gap and a variable valve angle have been studied. In case of the studied valve, opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…When considering the pressure losses in the numerical simulation of catheter configuration A, the pressure losses of the valves appeared to be twice as high as from the catheter itself. New valve designs are under construction (18) to decrease pressure losses. As a result, smaller catheters can be applied.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the pressure losses in the numerical simulation of catheter configuration A, the pressure losses of the valves appeared to be twice as high as from the catheter itself. New valve designs are under construction (18) to decrease pressure losses. As a result, smaller catheters can be applied.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the occurrence of haemolysis by shear stress depends not only on the shear stress level but also on the duration of the shear stress. 24,25 Studies have shown that blood is transported in a laminar flow in all vessels throughout the human body. The highest measured speed is 1,175 mm/s in the femoral artery with a diameter of 5 mm.…”
Section: Resistance Of Erythrocytesmentioning
confidence: 99%
“…By means of a guiding catheter, the tip of the catheter is introduced via peripheral arteries or open thorax into the left ventricle. The pump aspirates at least 3 L/min blood from the left ventricle and ejects it into the aorta (Morsink et al, 1997). The PUCA pump has a pneumatic driving system, which is electrocardiogram-triggered.…”
Section: The Puca-pump Project: a Case Studymentioning
confidence: 99%